The Role of Islamic Religious Education Teachers Through ICT-Based Learning Media Design in Improving Student Learning Outcomes at Smpn 4 Pinrang - Latami, Nurmiyati (IAIN Parepare, 2023)
This study discusses the Role of Islamic Education Teachers through the design of ICT-Based Learning Media. This study aims to determine the use of ICT-based learning media in SMP Negeri 4 Pinrang. This study used a type of descriptive qualitative research. With a case study approach, data sources are primary data (teachers, principals, vice principals) and secondary data (documents directly to the field or carried out in the field through observation, interviews, and documentation studies, in order to obtain clear and representative data. The results of this study show, (1) Islamic Religious Education learning tools used by Islamic Religious Education Teachers at SMP Negeri 4 Pinrang are learning tools that have been integrated with the latest curriculum, namely the independent curriculum. The intended learning tool design includes learning design, which begins with learning preparation which includes syllabus, preparation of lesson plans, and also the selection of methods and strategies. The learning design consists of three parts including preliminary activities, core activities after that closing and continued assessment for students. (2) The use of Information Communication and Technology (ICT)-based learning media used at SMP Negeri 4 Pinrang includes the use of hardware and software. The intended use of hardware is the use of laptops / computers, smartphones, active speakers / sound and LCD / projectors, while the use of software is powerpoint, internet, web, video editing applications, and youtube. (3) Learning Outcomes Students using ICT learning media based on the results of formative and summative assessments / assessments carried out by teachers to students show effectiveness in learning that produces or shows to improve student learning outcomes.